HIGH-TEMPERATURE CARBON REDUCTION OF SILICA: A NOVEL APPROACH FOR OXYGEN ISOTOPE ANALYSIS OF BIOGENIC OPAL - Lücke A.; Moschen R.; Schleser G.H. (My University, 2005)
A new technique has been developed for the determination of the oxygen isotope composition from biogenic silica. The iHTR method (inductive high temperature carbon reduction) is based on the reduction of silica by carbon with temperatures of up to 1830°C (maximum T 2200°C) to produce carbon monoxide for isotope analysis. Basically, samples of silica are mixed with graphite and filled into a sample holder made of a glassy carbon rod. The rod is introduced into a glassy carbon cylinder liner closed at the top which itself is enclosed by a double-walled glass vessel. The glassy carbon rod is inductively heated under vacuum to the temperature needed for quantitative conversion of the particular silica material to CO. The most critical process of dehydration (in the case of opal) and reduction to CO is routinely achieved in the iHTR device. Weakly bound oxygen and oxygen-containing contaminants, like hydroxyl groups, as well as remaining minor organic constituents are volatilized stepwise under high vacuum at temperatures of 850°C and 1050°C without isotopic exchange before the reduction of the silica. After completion of dehydration, the temperature is raised to the value needed for silica reduction. For both biogenic silica and quartz a temperature of 1550°C was found to be adequate. The technical design with a standard preparation routine and various test experiments is presented proving the reliability and capability of the new iHTR method, especially with respect to fresh diatom materials and diatom opal. The amount of sample material necessary at present is ∼1.5 mg of silica and the reproducibility achieved for natural samples is better than ±0.15‰. Replicate analysis of the quartz standard NBS28 resulted in a δ18O value of 9.62‰ ± 0.11‰ (n = 17).
Keywords: oxygen isotope; biogenic silica; opal